2023
DOI: 10.1128/iai.00012-23
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Colistin Resistance on the Activation of Innate Immunity by Lipopolysaccharide Modification

Abstract: Colistin resistance is acquired by different lipopolysaccharide (LPS) modifications. We proposed to evaluate the of effect in vivo colistin resistance acquisition on the innate immune response.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Proteus mirabilis exhibited the highest colistin resistance (16/16; 100%) which may be due to the modification of LPS of outer membrane. 42 The frequency of colistin resistance among other Enterobacterales species was 23.1% (6/26) for Enterobacter aerogenes, 13% (6/46) for E. coli, and 11.1% (8/72) for K. pneumoniae. In another publication by Mahmoud et al 43 in Egypt, colistin resistance appeared in 42.9% of K. pneumoniae and E. coli isolates.…”
Section: Discussionmentioning
confidence: 93%
“…Proteus mirabilis exhibited the highest colistin resistance (16/16; 100%) which may be due to the modification of LPS of outer membrane. 42 The frequency of colistin resistance among other Enterobacterales species was 23.1% (6/26) for Enterobacter aerogenes, 13% (6/46) for E. coli, and 11.1% (8/72) for K. pneumoniae. In another publication by Mahmoud et al 43 in Egypt, colistin resistance appeared in 42.9% of K. pneumoniae and E. coli isolates.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown decreased fitness and attenuated cytokine production in a Galleria mellonella infection model and reduced cytokine production in human-derived THP-1 cells infected with Escherichia coli expressing mcr-1 ( 14 ). Other modifications to LPS that confer colistin resistance, such as adding 4-amino-4-deoxy-l-arabinose (Ara4N), have been shown to enhance intracellular survival after phagocytosis and promote inflammatory signaling ( 15 ). In this study, we show that KP strains harboring the mcr-1 plasmid have an increased resistance to colistin with differential production of cytokines in human monocytes in vitro .…”
Section: Introductionmentioning
confidence: 99%